2012
DOI: 10.1098/rstb.2011.0287
|View full text |Cite
|
Sign up to set email alerts
|

Gene duplication, tissue-specific gene expression and sexual conflict in stalk-eyed flies (Diopsidae)

Abstract: Gene duplication provides an essential source of novel genetic material to facilitate rapid morphological evolution. Traits involved in reproduction and sexual dimorphism represent some of the fastest evolving traits in nature, and gene duplication is intricately involved in the origin and evolution of these traits. Here, we review genomic research on stalk-eyed flies (Diopsidae) that has been used to examine the extent of gene duplication and its role in the genetic architecture of sexual dimorphism. Stalk-ey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 149 publications
3
23
0
Order By: Relevance
“…Such tools may also inform us about sex differences in intrasexual competition, as different hormones and other mechanisms may be related to aggressive interactions in males and females [55,56]. Similarly, as Baker et al [57] demonstrate here, new genomic tools used to study genetic architecture and gene expression will be valuable for not only understanding female choice, but also sexual conflict, sexual dimorphism and other topics related to trait evolution.…”
Section: Competition Choice and The Futurementioning
confidence: 66%
“…Such tools may also inform us about sex differences in intrasexual competition, as different hormones and other mechanisms may be related to aggressive interactions in males and females [55,56]. Similarly, as Baker et al [57] demonstrate here, new genomic tools used to study genetic architecture and gene expression will be valuable for not only understanding female choice, but also sexual conflict, sexual dimorphism and other topics related to trait evolution.…”
Section: Competition Choice and The Futurementioning
confidence: 66%
“…Because 90% of the annotated X-linked genes in T. dalmanni are found on chromosome arm 2L in D. melanogaster and 3R in A. gambiae [18], [52], we assume that genes on chromosome arm 2L in D. melanogaster were on an ancestral X chromosome and must have moved if they are now located on a T. dalmanni autosome. De novo assembly of RNA sequences from Illumina sequencing data obtained from testes and adult heads revealed that many gene movements involve a duplicate gene copy [67] as would be expected if movement is caused by retrotransposition. We then compared the pattern of sex-bias for genes inferred to have moved onto or off the novel X using contingency table tests and either the distribution of genes on the autosomes or on the X as the expectation.…”
Section: Methodsmentioning
confidence: 90%
“…Analysis of the transcriptome from a wider array of tissues across development would help reveal the extent to which additional genes that affect eyestalks exhibit pleiotropic effects. Gene duplication, in particular, may provide a powerful mechanism for resolving sexual conflict [23] and a recent analysis of RNA-seq data in T. dalmanni revealed that genes that have duplicated in stalk-eyed flies are more likely to exhibit sex-biased gene expression [67].…”
Section: Discussionmentioning
confidence: 99%
“…Rapid evolution of young and novel genes is a feature also shared by sex-biased and sex-related genes, especially male reproductive genes, and is often attributed to positive selection [Wyckoff et al, 2000;Swanson and Vacquier, 2002;Haerty et al, 2007]. Studies have shown that duplicated genes can evolve new male-specific functions [Torgerson and Singh, 2004;Duncan et al, 2011;Chen et al, 2012] and are correlated with male-biased and male-specific genes in Caenorhabditis [Cutter and Ward, 2005], Drosophila [Gnad and Parsch, 2006;Wyman et al, 2012], and Teleopsis [Baker et al, 2012]. The degree to which duplicated genes contribute to sex-biased gene expression in most other organisms is not known.…”
mentioning
confidence: 99%